A novel NKX2–5 double variant corresponds with familial atrial septal defect with arrhythmia in Indonesia. (14th October 2021) - Rozqie, R; Satwiko, M G; Anggrahini, D W; Hartopo, A B; Sadewa, A H; Mumpuni, H; Dinarti, L K
Abstract: Background: The transcription factor NKX2–5 is essential for heart development during embryonic stages. The genetic variant of NKX2–5 is founded in many congenital heart diseases, especially atrial septal defect (ASD). Most of NKX2–5 variants in Asia based on Chinese population are single nucleotide polymorphisms. Whether the same variant of NKX2–5 is also involved in Southeast Asia population is still unknown. Therefore, we investigate the NKX2–5 variant in atrial septal defect population in Indonesia. Purpose: To investigate the genetic variation of NKX2–5 in ASD in Indonesian population. Methods: We screened 97 patients with ASD (including 23 familial patients) for sequence variant in NKX2–5. DNA samples were extracted from venous blood samples. The whole two coding exons of the NKX2–5 gene from DNA samples were amplified by multiplex PCR and directly sequenced. Variations were detected by comparison with the standard reference genome. The distribution of genotype frequency in atrial septal disease familial and non-familial were analyzed. Results: We identified a novel heterozygous DNA sequence double variant (c413 G>A, rs1366528649 and c561 G>C, rs767559311) in exon 2 of NKX2–5 gene was identified only in 3 familial ASD patients. These patients are related to first-degree relatives. Patients with these double variants have septal defects and arrhythmias in young-to middle-aged adults (sinus node dysfunction dan atrial tachycardia). Moreover, one reported single nucleotide polymorphisms (SNPs) (c63 A>G, rs2277923) was detected in 83 patients (85.6%), as 20 patients (87%) were present among the familial group, and 63 patients (85.1%) were found from the non-familial group. The distribution of rs2277923 variation among the familial and non-familial groups was not different. Variation of rs2277923 has 2 genotypes: homozygous AG presented in 42 patients (43.3%) and heterozygous AG shown in 41 patients (42.3%). The distribution of both genotypes is also similar between familial and non-familial groups. Conclusions: We discovered that the novel NKX2–5 double variants (rs1366528649 and rs767559311) might contribute to familial ASD risk, although the rs2277923 is the most commonly found variant in ASD patients in Indonesia. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Dana Masyarakat Faculty of Medicine, Public Health and Nursing UGM fiscal years 2020